Photosynthetic activity in both algae and cyanobacteria changes in response to cues of predation - Grzesiuk, Małgorzata; Pietrzak, Barbara; Wacker, Alexander; Pijanowska, Joanna (Frontiers in Plant Science, 2022)
A plethora of adaptive responses to predation have been described in microscopic aquatic producers. Although energetic costs of these responses are expected, with their consequences going far beyond individual, their underlying molecular and metabolic mechanisms are not fully known. One, so far hardly considered, is if and how the photosynthetic efficiency of phytoplankton might change in response to predation cues. Our main aim was to identify such responses in phytoplankton and to detect if these are taxon-specific. We exposed seven algae and seven cyanobacteria species to the chemical cues of an efficient consumer Daphnia magna, which was fed either a green alga Acutodesmus obliquus or a cyanobacterium Synechococcus elongatus (kairomone and alarm cues) or was not feeding (kairomone alone). In most algal and cyanobacterial species studied the yield of photosystem II increased in response to predator fed cyanobacterium, whereas in most of these species the yield did not change in response to predator fed alga. Also, cyanobacteria tended not to respond to a non-feeding predator. The modal qualitative responses of the electron transport rate were similar to that of the quantum yield. To our best knowledge, the results presented here are the broadest scan of photosystem II responses in the predation context so far.